"The Baby of the Government" : a case study of the implementation of the Massive Food Production Programme and genetically modified maize into smallholder farming in rural South Africa - Nilsson, Anna; Karlsson, Hanna (SLU/Dept. of Urban and Rural Development, 2008)
Massive Food Production Programme (MFPP) is a development programme initiated by the South African state with the aim of increasing the agricultural production and generating economic development. The initial plan of the programme was to improve the quality of life in rural areas by changing the smallholders' agricultural techniques and make them adopt methods of industrial agriculture and modern seed varieties. The agro-chemical company Monsanto has an important role in MFPP, as an input supplier as well as a provider of technical advice. In some of the villages that participated in MFPP the smallholders have been growing genetically modified maize, as did the villagers in Xopozo. Xopozo is a rural village in the province Eastern Cape where part of the fieldwork of this study was made. The purpose of this study is to investigate how the objectives, implementation and results of MFPP have been interpreted by different actors. MFPP has failed or been stopped before the planned ending date in many villages where it was implemented. We attempted to analyse the reasons for this failure. The study also includes an analysis of the introduction of genetically modified crops in MFPP, how this corresponds with the objectives and how the usage was interpreted by different actors in MFPP. The study is based on interviews with officials at different levels within the Eastern Cape Department of Agriculture (ECDA), agricultural extension officers involved in MFPP representatives form Monsanto and villagers in Xopozo. The methods employed are mainly semi-structured interviews but also PRA methods and observations. Our conclusion is that MFPP is a top-down planned programme, and that there has not been any possibility for the participating smallholders to affect its planning or implementation. Lack of information within MFPP explains a part of the failure of the programme. The actors interpreted the objectives and the purpose of the programme in different ways. The lack of information and participation from smallholders are important factors to why MFPP failed. Another important factor behind the failure are the views on poverty and development coming from the ECDA. MFPP is merely offering technical solutions in form of increased food production. Because of the focus of increasing food production genetically modified crops match the objectives of MFPP. This focus in combination with the views about poor people as lazy, passive and irrational has contributed to the failure of MFPP.